Personality-guided relational psychotherapy : a unified approach - Magnavita, Jeffrey J. (Personality-guided psychology / series editor Theodore Millon, 2005)
(from the publicity materials) In Personality-Guided Relational Therapy author Jeffrey J. Magnavita demonstrates how personality theory guides his approach to psychotherapy. His empirically founded new model provides a flexible and evolving theory and approach to therapy that draws from more than a century of developments in the field of psychology. This book reconciles and integrates several theoretical viewpoints, enabling clinicians to conceptualize clinical syndromes by understanding the complex interplay of elements from the biopsychosocial model. Further, case illustrations demonstrate the theory, methods, and techniques of treatment. Beginning with an overview of the conceptual domains integrated here (affective, cognitive, defensive, neurobiological), and an explanation of why such integration makes sense, Dr. Magnavita moves on to describe his theoretical formulation, its component systems, the developmental progression, and several levels of treatment intervention, moving logically from the individual through the dyad, triad, and larger groups. The book culminates in an integrative chapter devoted to enhancing treatment synergy and a final chapter focused on empirical verification and future directions. This volume is part of the Ted Millon's Personality-Guided Psychology series.